Acessibilidade e longitudinalidade no pré-natal: análise de um grupo de puérperas atendidas no hospital universitário Cassiano Antônio de Moraes - Neder, Anderson Gabriel (2013)
The primary care goals wide coverage and access to comprehensive and acceptable health care services. It lays emphasis on prevention and education (STARFIELD, 2004). In Brazil, the Estratégia Saúde da Familia (ESF) is the model developed by the Ministry of Health (MOH) for the purpose of restructuring of primary care. It covers about 50 % of the population. According Starfield (2004) primary care can be assessed by its essential attributes: first-contact care (accessibility and utilization), longitudinality, comprehensiveness and coordination of care. In the context of the Brazilian health care, child mortality is still a disturbing fact, especially mortality occurring in the first days of life. This component of mortality is closely related to quality of care received during pregnancy. The prenatal care should include organized, large, integrated and comprehensive actions. It should provide health promotion and prevention, diagnosis and treatment of problems that may occur during this period. The purpose of this study was to analyze the attributes of primary care accessibility and longitudinality in a group of women treated in HUCAM. To achieve this objective was conducted interviews with 80 women who received prenatal care in primary care and 19 women who received prenatal care at the Hospital Universitário Cassiano Antonio de Moraes (HUCAM). It was used partial evaluation questionnaire of primary PCATool. The women were also questioned about their perception of the adequacy of prenatal care. Accessibility was low for most subjects in primary care. Accessibility was statistically higher in women who received prenatal care in the ESF and those who used health facilities in the city of Vitória (ES). The longitudinality was related to the type of health facility prenatal, the number of medical visits and the Apgar score in the first minute. The perception of an adequate prenatal care was associated with the use of the ESF as prenatal service and the attainment of six or more medical visits. In the group that underwent prenatal care in HUCAM, Although postpartum women of the group that performed the prenatal HUCAM realize the prenatal care as appropriate, some questions revealed fragilities in care, particularly regarding the access to the service. The inability to receive care by the medical staff outside the opening hours of the clinic, the lack of a phone number where they can answer questions or talk to the doctor responsible for prenatal, perception of difficulty in scheduling appointments and long waiting periods on the day of consultation are points that should be improved in this care